Worldwide Phylogenetic Group Patterns of Escherichia coli from Commensal Human and Wastewater Treatment Plant Isolates - Stoppe, Nancy de Castro; Silva, Juliana S.; Carlos, Camila; Sato, Maria I. Z.; Saraiva, Antonio M.; Ottoboni, Laura M. M.; Torres, Tatiana T. (Frontiers in Microbiology, 2017)
Escherichia coli is an important microorganism in the gastrointestinal tract of warm-blooded animals. Commensal populations of E. coli consist of stable genetic isolates, which means that each individual has only one phylogenetic group (phylogroup). We evaluated the frequency of human commensal E. coli phylogroups from 116 people and observed that the majority of isolates belonged to group A. We also evaluated the frequency of phylogroups in wastewater samples and found a strong positive correlation between the phylogroup distribution in wastewater and human hosts. In order to find out if some factors, such as geographical location, and climate could influence the worldwide phylogroup distribution, we performed a meta-analysis of 39 different studies and 24 countries, including different climates, living areas, and feeding habits. Unexpectedly, our results showed no substructuring patterns of phylogroups; indicating there was no correlation between phylogroup distribution and geographic location, climate, living area, feeding habits, or date of collection.